1999
DOI: 10.1007/bf03161733
|View full text |Cite
|
Sign up to set email alerts
|

Soil indicators of agricultural impacts on northern prairie wetlands: Cottonwood lake research area, north Dakota, USA

Abstract: Potential damage to wetlands by lmld-use practices has prompted a need for relatively inexpensive, reliable indicators in monitoring ecological conditions. In this study, soil classification and the following soil tests, sodium bicarbonate-extractable P, nitrate (NO~-), organic matter fOM), pH, electrical conductivity (EC), and '-'TCs distribution, were used to compare four wetlands surrounded by cultivated land or grassland.Cumulic A horizons greater than 60-cm thick were found covering the wet meadow zone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Prairie cordgrass habitat is typically wet lowland areas with moderate salinity (Freeland et al 1999;Redmann 1972). Prairie cordgrass habitat is frequently a monoculture but can overlap with switchgrass and big bluestem (Tatina 1994;Weaver and Darland 1944).…”
Section: Resultsmentioning
confidence: 99%
“…Prairie cordgrass habitat is typically wet lowland areas with moderate salinity (Freeland et al 1999;Redmann 1972). Prairie cordgrass habitat is frequently a monoculture but can overlap with switchgrass and big bluestem (Tatina 1994;Weaver and Darland 1944).…”
Section: Resultsmentioning
confidence: 99%
“…Human disturbances to wetlands are frequently the result of agricultural practices and urban development ͑Adamus and Brandt 1990; Cole et al 1997;Freeland et al 1999;Galatowitsch et al 2000͒, and their impacts can be divided into individual stressors that may have physical, chemical, and/or biological effects on wetlands. Sedimentation is an important stressor in wetlands because it affects the ability of seeds to germinate and establish ͑Jurik et al 1994;Wardrop and Brooks 1998͒ by altering light availability, temperature, and oxygen levels in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Craft and Casey (2000) found that deposition in Georgia wetlands was dependent on past and current anthropogenic disturbance within the surrounding watershed. Freeland et al (1999) found that there were higher rates of deposition in wetlands adjacent to cultivated fields in North Dakota. Sediments and nutrients deposited in wetlands impact the vegetation and hydrology of the systems (Mahaney et al 2005;Preston et al 2013).…”
Section: Soil Change In Wetlandsmentioning
confidence: 95%